Interaction of phenytoin and primidone. Issue 5971 (14th June 1975) - Reynolds, E H; Fenton, G; Fenwick, P; Johnson, A L; Laundy, M
Abstract : The ratio of derived phenobarbitone to unmetabolized primidone in the serum was significantly higher in 50 epileptic patients on a combination of primidone and phenytoin than in 12 patients on primidone alone, though the dose and serum levels of primidone were similar in the two groups. Out of 253 patients attending a seizure clinic 47% were taking a combination of these two anticonvulsants. The effect of phenytoin on the metabolism of primidone may have clinical implications in view of the frequency of their combined use.